OBESITY AS A MODIFIABLE DETERMINANT OF THYROID DYSFUNCTION, STRUCTURAL CHANGES, AND THYROID CANCER - Klaudia Baran; Aleksandra Grygorowicz; Michał Ględa; Michał Szyszka; Weronika Radecka; Weronika Kozak; Agnieszka Szreiber; Karol Grela; Karolina Nowacka; Kamil Jabłoński; Anna Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Obesity has become a global health problem with rapidly increasing prevalence across all age groups. Accumulating evidence suggests that excess adiposity affects thyroid function and morphology and may contribute to the rising incidence of thyroid cancer. This review summarizes current knowledge on the interplay between obesity, thyroid physiology, thyroid structural alterations, and thyroid cancer risk.Methods: A comprehensive literature search was conducted using PubMed and Google Scholar, focusing on systematic reviews and meta-analyses. Keywords such as “obesity”, “body mass index”, “thyroid nodules”, “thyroid cancer”, “bariatric surgery”, and “GLP-1 RA” guided the search. Selected studies were qualitatively analyzed.Results: Obesity was strongly associated with elevated TSH, thyroid hypertrophy, increased thyroid volume, and higher prevalence of nodules, often with more suspicious cytology. Meta-analyses showed that each 5-unit increase in BMI corresponds to an increase up to a 30% in thyroid cancer risk, particularly for papillary, follicular, and anaplastic subtypes. Mechanisms include hyperleptinemia, chronic inflammation, insulin resistance, altered estrogen signaling, and oxidative stress. Weight-loss interventions, including bariatric surgery and GLP-1 receptor agonists, were associated with the improvements of thyroid function and morphology.Conclusions: Obesity is a significant and modifiable determinant of thyroid dysfunction and thyroid cancer. Effective weight management may reverse obesity-related thyroid alterations and should be integrated into clinical care and preventive strategies.